2015
DOI: 10.1007/s11999-014-3976-0
|View full text |Cite
|
Sign up to set email alerts
|

Large-diameter Metal-on-metal Total Hip Arthroplasty: Dislocation Infrequent but Survivorship Poor

Abstract: Level IV, Therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 60 publications
0
29
0
3
Order By: Relevance
“…This finding may also be related to increased failure of MoM hips in this subset of the Medicare patient population. A study by Lombardi et al [27] of 1235 patients with a mean age of 58 years reported an increased risk of revision of large-diameter MoM THAs in younger patients. However, in that study, female patients were more likely to have failure of their MoM THA than male patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding may also be related to increased failure of MoM hips in this subset of the Medicare patient population. A study by Lombardi et al [27] of 1235 patients with a mean age of 58 years reported an increased risk of revision of large-diameter MoM THAs in younger patients. However, in that study, female patients were more likely to have failure of their MoM THA than male patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the MoM group had more male patients and a lower proportion of patients in the older age ranges. This may be the result of surgical selection bias in the mid-2000s with implantation of more MoM hips in younger male patients, because this bearing surface was anticipated to have less wear and osteolysis compared with MoP components [27]. This finding may also be related to increased failure of MoM hips in this subset of the Medicare patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike large-diameter MoM THA, in which aseptic loosening and early failure of ingrowth appear to be the main failure modes with ARMD appearing in the early to midterm, MoM THA with a titanium shell and cobalt-chromium insert had very low rates of aseptic loosening. In a study from our center of large-diameter MoM THA from the same manufacturer as the current study device (Magnum and M2a-38; Zimmer Biomet), the frequency of ARMD was 3% (47 of 1440) and aseptic loosening was 2% (34 of 1440) at a mean followup of 7 years (range, 2-12 years) [28]. In comparison, in the current study the frequency of ARMD was 5% (14 of 300) at a mean followup of 10 years (range, 2-19 years), but frequency of revision for aseptic loosening was much lower at 1% (four of 300).…”
Section: Discussionmentioning
confidence: 92%
“…In an effort to further improve stability and reduce frequency of dislocation, use of small-diameter MoM bearings gave way to MoM designs with increasing head diameters. However, large head MoM THAs have exhibited high rates of loosening and adverse reactions to metal debris (ARMD) with many failures occurring early [1,6,13,17,18,26,28,37,46,52]. We recently reported our results with large head MoM THA at minimum 2-year followup (mean, 7 years; range, 2-12 years) and observed a higher than expected rate of revision (7.5% [108 of 1440]) with the majority of failures secondary to ARMD (48% [47 of 108]) and lack of ingrowth (31% [34 of 108]) [28].…”
Section: Introductionmentioning
confidence: 99%